Minimalist model systems reveal similarities and differences between membrane interaction modes of MCL1 and BAK - Landeta, Olatz; Landajuela, Ane; García-Sáez, Ana J.; Basañez, Gorka (The journal of biological chemistry, 2015)
Proteins belonging to the BCL2 family are key modulators of apoptosis that establish a complex network of interactions among themselves and with other cellular factors to regulate cell fate. It is well established that mitochondrial membranes are the main locus of action of all BCL2 family proteins, but it is difficult to obtain a precise view of how BCL2 family members operate at the native mitochondrial membrane environment during apoptosis. Here, we used minimalist model systems and multiple fluorescence-based techniques to examine selected membrane activities of MCL1 and BAK under apoptotic-like conditions. We show that three distinct apoptosis-related factors (i.e. the BCL2 homology 3 ligand cBID, the mitochondrion-specific lipid cardiolipin, and membrane geometrical curvature) all promote membrane association of BCL2-like structural folds belonging to both MCL1 and BAK. However, at the same time, the two proteins exhibited distinguishing features in their membrane association modes under apoptotic-like conditions. In addition, scanning fluorescence cross-correlation spectroscopy and FRET measurements revealed that the BCL2-like structural fold of MCL1, but not that of BAK, forms stable heterodimeric complexes with cBID in a manner adjustable by membrane cardiolipin content and curvature degree. Our results add significantly to a growing body of evidence indicating that the mitochondrial membrane environment plays a complex and active role in the mode of action of BCL2 family proteins.
Gesehen am 08.06.2020